Public Controversy in Viewing Covid-19 Information on Instagram - Purnamasari, Oktaviana; Putri, Puri Kusuma Dwi; Darmaputra, Riza; Rahim, Norhayati Rafida Abdul (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
The Covid-19 pandemic, which has been going on for more than two years, has left various problems affecting health, the economy, and the flow of information in society. The government of Indonesia and related parties are trying to educate the public about the importance of booster vaccines and sustainability in maintaining health protocols through mass media, one of which is online mass media such as Instagram. In order to see the pros and cons of uploaded comments related to Covid-19 information, this study aims to examine the comparison of public responses in responding to information about the Covid-19 pandemic on the doctor's accounts @adamprabata and Ministry of Health @kemenkes_ri on Instagram. This study used a qualitative approach with a virtual ethnographic method based on Cyber Media Analysis. The data for this study are taken through observations from the two Instagram accounts related to information about Covid-19 in October - November 2022. This timeframe is chosen to see how the public perceives information related to Covid-19 when the Covid-19 pandemic has started to subside. However, there is concern that the number of sufferers will increase due to the emergence of the XBB subvariant. The results of the research show that ordinary people perceive Covid-19 as does not exist anymore. Thus, health protocol and vaccines were no longer necessary. Meanwhile, people who have sought health information in more depth by following doctors' accounts who frequently discuss health issues, including Covid-19 from different perspective. They tend to be more careful about the Covid-19 situation during this period. Keywords: Controversy, Covid-19, Instagram, Pandemic, Public